The Distorting Effects of Corruption on Financial Stability and Economic Growth: Evidence from Russian Banks Using a PVAR Approach. Issue 3 (4th May 2022) - Papadamou, Stephanos; Papadopoulos, Symeon; Pitsilkas, Konstantinos
ABSTRACT: In this study, we use a panel vector autoregression approach to investigate how financial stability, measured by nonperforming loans (NPLs), interacts with profitability, leverage, loan growth, and economic growth in an improving or worsening corruption framework. The results underline the effects of changes in corruption on banks' management quality and on the time-persistence of NPLs. A shock to NPLs reduces profitability, loan growth, and GDP. In a worsening corruption environment, these effects are stronger and more time-persistent, confirming the distorting effects of corruption on financial stability and growth. In contrast, NPLs decline due to a shock to profitability, leverage, and GDP.